Phase composition evolution of co-precipitated zirconium and yttrium hydroxides during heat treatment - Gabelkov, S.V.; Tarasov, R.V.; Poltavtsev, N.S.; Belkin, F.V. (Functional Materials, 2009)
Formation of complex amorphous hydroxide at co-precipitation of zirconium and yttrium hydroxides has been investigated by X-ray phase analysis and thermal analysis. Its thermal decomposition occurs in a single stage in the temperature interval 20-400°C and results in formation of amorphous zirconia. Parameters of amorphous zirconia "halo" are determined and absence of their dependence on the precursor compound and mass content of yttrium oxide is established. Crystallization temperature of amorphous zirconia (500 to 600°C), average size of coherent-scattering region (28±3 nm) and crystal structure of the phase obtained have been determined. The phase composition evolution depending on heat treatment temperature has been traced in the sequence complex amorphous zirconium/yttrium hydroxide amorphous zirconia - tetragonal zirconia. In this case yttrium, while not forming independent phases, is successively a component of complex amorphous hydroxide, amorphous oxide and tetragonal zirconia.